Pendidikan Agama Kristen sebagai Landasan Etika Bermedia Sosial di Tengah Keberagaman - Elieser R. Marampa; Agustina Siburian; Kristian Sukatman; Eva Ros Lince Tambunan (Sekolah Tinggi Teologi Nusantara, 2026)
This study is motivated by the rapid development of digital technology, which has influenced patterns of communication and social interaction particularly on social media thereby giving rise to various ethical issues such as the spread of misinformation, hate speech, and cyberbullying within a diverse society. This situation underscores the importance of an ethical foundation for fostering responsible social media behavior. This study aims to analyze the contribution of Christian Religious Education as an ethical foundation for social media use amidst diversity. The method used is a qualitative approach through a literature review, with data collected from books, journal articles, and relevant documents, analyzed using content analysis techniques. The results of the study indicate that CRE plays a role in shaping social media ethics through the instillation of values such as love, honesty, responsibility, and tolerance, which are manifested in digital awareness, an attitude of respecting differences, and wise digital literacy skills. Thus, CREserves as a foundation for fostering ethical, responsible, and civilized social media behavior. AbstrakPenelitian ini dilatarbelakangi oleh pesatnya perkembangan teknologi digital yang memengaruhi pola komunikasi dan interaksi sosial secara khususnya penggunaan media sosial yang sering memunculkan berbagai persoalan etika seperti penyebaran hoaks, ujaran kebencian, dan perundungan siber di tengah masyarakat yang beragam. Kondisi ini menunjukkan pentingnya landasan etis untuk membentuk perilaku bermedia sosial yang bertanggung jawab. Penelitian ini bertujuan menganalisis Pendidikan Agama Kristen sebagai landasan etika bermedia sosial di tengah keberagaman. Metode yang digunakan adalah pendekatan kualitatif melalui studi kepustakaan dengan pengumpulan data dari buku, artikel jurnal, dan dokumen relevan, yang dianalisis menggunakan teknik analisis konten. Hasil penelitian menunjukkan bahwa Pendidikan Agama Kristen berperan penting dalam membentuk etika bermedia sosial melalui penanaman nilai kasih, kejujuran, tanggung jawab, dan toleransi, yang diwujudkan dalam kesadaran digital, sikap menghargai perbedaan, serta kemampuan literasi digital yang bijak. Kata Kunci: Pendidikan Agama Kristen; Etika Bermedia Sosial;